(Don’t) let your hair down: the role model influence on black women’s adoption of beauty standards - Melo, Aline Menezes (2018)
In addition to the multiple types of prejudice historically encountered by black people in general, black women also suffer discrimination on the grounds of image and beauty. Intimately connected to their social identity, this prejudice permeates many aspects of their lives, including consumption choices and willingness to steer clear from black standards to follow white beauty standards. One markedly known practice along these lines refers to the use of chemicals to straighten the curly hair black women naturally have. However, role models in the form of ingroup women in power position can be a way to disconfirm the negative stereotypes black women hold about themselves and thereby reduce this widespread practice. This article sheds light on the effect of role model and stereotype threat on black women’s adoption of an ingroup beauty standard (i.e., choice of a curly or kinky hair product set). Results of an online experiment provide evidence for the positive effect of role model on the decision to choose an ingroup product. Importantly, this effect is moderated by stereotype threat such that role model exerts greater influence on ingroup product choice when threats are salient. Implications for practice and future research are also discussed.